FUNGSI PIMPINAN BAGIAN PEMBERITAAN PADA LPP TVRI STASIUN RIAU - Saputra, Sakti Novrian; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The development of television as a provider of information has progressed rapidly. Television as a means of providing information for people who need information, both nationally and internationally. The information presented is useful for users to increase knowledge or only as a medium for entertainment. The good news or television program can not be separated from the leadership function that goes well to direct employees to get quality news and events. This study aims to identify and understand the function of the leadership directed by the news leader which consists of the functions of instruction, consultation, participation, delegation and control. Is this function running well in the news section of LPP TVRI Riau Station?This study uses a qualitative research method using a descriptive approach, which is a research process and understanding based on a research methodology that investigates a social phenomenon and human problem. The informants in this study were 5 people who were taken based on the snowball technique. Data collection techniques were carried out through field observations, interviews, and documentation. The data analysis technique uses a comparative descriptive analysis model, namely the data analysis is carried out interactively and takes place continuously until it is complete so that the data is saturated. Techniques for checking the validity of the data using triangulation and negative case analysis.This research was conducted based on the results of observations (observations), interviews and documentation, it can be concluded that the leadership function is in accordance with the concept of Rivai (2012), which at LPP TVRI Riau Station has implemented a leadership function such as the leadership instruction function where the leader always provides motivation to mobilizing others to carry out orders from superiors, in the consulting function the leadership provides positive input to find a way out of the reporting problems faced, during operational preparation and implementation, the leadership participates in providing and releasing employees for spaciousness, at the time of reporting employees are given delegation of authority at work, and during reporting and broadcasting activities, the leadership has carried out control according to the SOPs at LPP TVRI Riau Station.